Optimizing K0.5Na0.5NbO3 Single Crystal by Engineering Piezoelectric Anisotropy - Weixiong Li; Chunxu Chen; Guangzhong Xie; Yuanjie Su (Nanomaterials, 2021)
K0.5Na0.5NbO3 is considered as one of the most promising lead-free piezoelectric ceramics in the field of wearable electronics because of its excellent piezoelectric properties and environmental friendliness. In this work, the temperature-dependent longitudinal piezoelectric coefficient <semantics><msubsup>d33*</msubsup></semantics> was investigated in K0.5Na0.5NbO3 single crystals via the Landau–Ginzburg–Devonshire theory. Results show that the piezoelectric anisotropy varies with the temperature and the maximum of <semantics><msubsup>d33max*</msubsup></semantics> deviates from the polar direction of the ferroelectric phase. In the tetragonal phase, <semantics><msubsup>d33maxt*</msubsup></semantics> parallels with cubic polarization direction near the tetragonal-cubic transition region, and then gradually switches toward the nonpolar direction with decreasing temperatures. The maximum of <semantics><msubsup>d33o*</msubsup></semantics> in the orthorhombic phase reveals a distinct varying trend in different crystal planes. As for the rhombohedral phase, slight fluctuation of the maximum of <semantics><msubsup>d33r*</msubsup></semantics> was observed and delivered a more stable temperature-dependent maximum <semantics><msubsup>d33maxr*</msubsup></semantics> and its corresponding angle θmax in comparison with tetragonal and orthorhombic phases. This work not only sheds some light on the temperature-dependent phase transitions, but also paves the way for the optimization of piezoelectric properties in piezoelectric materials and devices.